FAKTOR-FAKTOR YANG BERHUBUNGAN DENGANPEMILIHAN METODE KONTRASEPSI JANGKA PANJANG (MKJP) PADA WANITA USIA SUBUR DI DESA TAJURHALANGTAHUN 2019 - Meyrina Ika Faradita (2019)
This study was conducted to know one of the most effective efforts to controle the growth of inhabitant is by using contraception tools. The method of contraception widely use in indonesia is non Long term contraception method although Long term contraception method is more effective. So this situation give a big contribution to the failure of growth inhabitant controlled program. This research is done to analyze the factor which influence the selection of long term contraception method. The samples is taken by using sistematic random technique. The total sample are 145 respondent of familly planned acceptor. The independent variables are cost, the effect, the total of lived bith baby, education grade,control behavior perception, attitude to the manner, and subjective norm. Data was collected by using questionaire and double logistic regretion analyses. This result shows that the influenced variable is the total of lived birth baby (p.value = 0.022, OR= 0.272). While uninfluenced are the loss, education, control behavior perception, attitude to the manner and subjective norm. It can be conclude that the total of lived birth baby is the factorwhich can influence the selection of long term contraception method. Based on the result of this research , the society is suggested to accept the goverment Long term contraception method program. The goverment and the society helth service should work together to provide the facility and also give the information about Long term contraception method.